Diatoms as Bioindicators in Monitoring Water Quality, River Sosiani, Kenya - Namwaya , David W.; Raburu , Philip O.; Lunaligo , Lubanga (African Journal of Education,Science and Technology (AJEST), 2013)
The purpose of the study was to investigate the potential use of diatoms as biological monitors of environmental quality in Urban R. Sosianiin view of diatom distribution being affected by chemical, biological and physical characteristics of an aquatic system. In determination of Abundance, distribution and diversity of diatoms in relation to changing water quality variables, diatoms from benthic substrate in the riffle, littoral and the run with physical and chemical data were collected for a duration of six months from four strategically located sites covering a variety of anthropogenic activities along the river. Water quality parameters for instance total nitrogen whose changes are accounted for by the changing human activities but affecting diatom population were studied. During the study, a total of 9 diatoms genera unevenly distributed along the river were identified. In the upstream, the highest species diversity and relative abundance at 36.19% were recorded reducing to a relative abundance of 11.135% downstream. Pollution sensitive species; Gomphenema, Navicula and Tabellariasp were identified in the upstream while pollution tolerant species among them Melosira and Nitzchiadominating downstream that was characterized with high nutrient levels. It is reputable that human activities influenced water quality along the river continuum accredited to the changing human activities and water quality parameters resulting to less species diversity downstream necessitating pollution management measures unavoidable